Pengalaman Tenaga Kesehatan dalam Melakukan Tes HIV pada Ibu Hamil di Puskesmas - Rita Ismail; Nurdahlia Nurdahlia; Titi Sulastri; Santa Manurung; Syafdewiyani Syafdewiyani; Sri Yona (Poltekkes Kemenkes Jakarta III, 2023)
The number of new HIV cases in DKI Jakarta is increasing every year. The East Jakarta has the highest incidence of HIV cases. The increasing number of HIV cases is not followed by awareness of HIV test, especially pregnant women. The purpose of this study was to obtain an overview of the experience of health care providers in performing HIV tests on pregnant women. The research method was descriptive narrative with participants from health workers who did HIV tests on pregnant women. The research was conducted at two Community Health Center in East Jakarta. Interviews used structured questions, conducted for 30 – 55 minutes, and recorded using a digital voice recorder with 13 participants. The data were analyzed using content analysis techniques. The four themes emerged including HIV test was mandatory for pregnant women at the first visit (K1); emphasizing on explaining the benefits of HIV test for prevention of HIV transmission in children; coordinating in the implementation HIV test for pregnant women and handling of those who are HIV positive; and challenges in implementing HIV test. in pregnant women. Health education about the importance of HIV test for pregnant women should be done from an early age. Additional of reagents HIV test for mothers from other regions is needed. The results of this study are expected to be input in improving the quality of HIV test for pregnant women.